3690884862

# 3690884862 - Chapter 2 Boolean Expression Simplification...

This preview shows pages 1–5. Sign up to view the full content.

CEG 260, Meilin Liu 1 Chapter 2 Boolean Expression Simplification using BooleanAlgebra Meilin Liu Department of Computer Science Wright State University Homepage: http://www.wright.edu Email: [email protected]

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
CEG 260, Meilin Liu 2 1. 3. 5. 7. 9. 11. 13. 15. 17. Commutative Associative Distributive DeMorgan’s 2. 4. 6. 8. X . 1 X = X . 0 0 = X . X X = 0 = X . X Boolean Algebra 10. 12. 14. 16. X + Y Y + X = ( X + Y ) Z + X + ( Y Z ) + = X ( Y + Z ) XY XZ + = X + Y X . Y = XY YX = ( XY ) Z X ( YZ ) = X + YZ ( X + Y )( X + Z ) = X . Y X + Y = X + 0 X = + X 1 1 = X + X X = 1 = X + X X = X
CEG 260, Meilin Liu 3 Boolean Expression Simplification by Boolean Algebra (1)X+XY = X Proof: X+XY = X*1 +XY = X(1+Y) = X (2)XY+XY’ = X Proof: XY+XY’ = X(Y+Y’) = X*1 = X (3)X+X’Y = X+Y Proof: X+X’Y = (X+X’)(X+Y) = X+Y (4)X(X+Y) = X Proof: X(X+Y) = X+XY = X*1+X*Y = X (1+Y) =X*1=X Extension: a(a+b+c)=aa+ab+ac=a+ab+ac=a*(1+b+c)=a

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
CEG 260, Meilin Liu 4 Boolean Expression Simplification by Boolean Algebra (5) (X+Y)(X+Y’) = X Proof: (X+Y)(X+Y’) = X+(Y*Y’) = X +0=X 2 nd Solution: (X+Y)(X+Y’)=X*X+XY’+Y*X+Y*Y’= X*1+XY’+XY+0=X*(1+Y’+Y)=X*1=X (6) X(X’+Y)=XY Proof: X(X’+Y) = (X*X’) +XY = 0+ XY=XY By taking duals on the both sides of equation (1),(2), (3), we got Equation (4), (5),(6)
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}

### Page1 / 14

3690884862 - Chapter 2 Boolean Expression Simplification...

This preview shows document pages 1 - 5. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online